PATOMORPHOLOGICAL AND HISTOCHEMICAL INDICES IN EXPERIMENTAL PNEUMONIA IN KARAKUL LAMBS OF UZBEKISTAN - Kh.B. Yunusov, B.A. Kuliyev , D.N. Fedotov (International Journal of Advanced Science and Technology, 2020)
The article establishes the role of Pasteurella, staphylococci and streptococci in the etiology of pneumonia in Karakul lambs in Uzbekistan. Pathomorphological and histochemical indicators are highlighted by the results of histological and histochemical research methods.